2014
DOI: 10.1017/s002428291400019x
|View full text |Cite
|
Sign up to set email alerts
|

Extended phylogeny and a revised generic classification of thePannariaceae(Peltigerales, Ascomycota)

Abstract: We estimated phylogeny in the lichen-forming ascomycete family Pannariaceae. We specifically modelled spatial (across-site) heterogeneity in nucleotide frequencies, as models not incorporating this heterogeneity were found to be inadequate for our data. Model adequacy was measured here as the ability of the model to reconstruct nucleotide diversity per site in the original sequence data. A potential non-orthologue in the internal transcribed spacer region (ITS) of Degelia plumbea was observed. We propose a rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
94
1
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(105 citation statements)
references
References 85 publications
(225 reference statements)
6
94
1
4
Order By: Relevance
“…As in earlier studies (Ekman et al 2014;Magain & Sérusiaux 2014), the genus Fuscopannaria is retrieved as a monophyletic group, divided into two strongly supported clades, accepting that F. sampaiana (Tav.) P. M. Jørg.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…As in earlier studies (Ekman et al 2014;Magain & Sérusiaux 2014), the genus Fuscopannaria is retrieved as a monophyletic group, divided into two strongly supported clades, accepting that F. sampaiana (Tav.) P. M. Jørg.…”
Section: Resultssupporting
confidence: 66%
“…P. M. Jørg. is assigned to a different genus (Nevesia: Ekman et al 2014) and with the exception of F. laceratula (Hue) P. M. Jørg. which is resolved within a strongly supported and related lineage comprising Protopannaria pezizoides P. M. Jørg.…”
Section: Resultsmentioning
confidence: 99%
“…Species that form bipartite symbioses with cyanobacteria are largely restricted to the Peltigerales, while cephalodiate taxa occur more sporadically among different lecanoromycete orders (Miadlikowska et al 2014). Most fungi in the Peltigerales (e.g., Collemataceae, Nephromataceae, Pannariaceae, and Peltigeraceae) associate with symbiotic Nostoc, while others (e.g., Coccocarpiaceae) associate with other nostocalean and/or stigonematalean cyanobionts (Lücking et al , 2013bEkman et al 2014;Spirbille et al 2014;Zúñiga et al 2015, see Rikkinen 2013 for more detailed review).…”
Section: Ascolichens and Basidiolichensmentioning
confidence: 99%
“…Based on phylogenetic analysis of DNA sequence data, Physma, Ramalodium and Leciophysma were assigned to the Pannariaceae by Wedin et al (2009) and Otálora et al (2010), who found evidence that the Collemataceae proper does not include any members with single-celled ascospores. Extrapolating from these results, Ekman et al (2014) provisionally treated also Leightoniella and Homothecium as members of the Pannariaceae. This treatment, however, remained unconfirmed as long as DNA sequence data were unavailable.…”
Section: Introductionmentioning
confidence: 97%